2017
DOI: 10.1016/j.chb.2017.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Latent-level relations between DSM-5 PTSD symptom clusters and problematic smartphone use

Abstract: Common mental health consequences following the experience of potentially traumatic events include Posttraumatic Stress Disorder (PTSD) and addictive behaviors. Problematic smartphone use is a newer manifestation of addictive behaviors. People with anxiety severity (such as PTSD) may be at risk for problematic smartphone use as a means of coping with their symptoms. Unique to our knowledge, we assessed relations between PTSD symptom clusters and problematic smartphone use. Participants (N = 347), recruited thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 75 publications
(115 reference statements)
5
30
0
1
Order By: Relevance
“…These findings concur with previous research that identified strong relations between PTSD severity and problematic technology use, specifically smartphone addiction (Contractor, Weiss, Tull, & Elhai, 2017). It has been suggested that PTSD and problematic smartphone use share common risk factors (Contractor, Frankfurt, Weiss, & Elhai, 2017), such as low self‐esteem, impulsivity, and neuroticism. A strong association has also been reported between PTSD severity and verbal aggression (Byrne & Riggs, 1996), and levels of verbal aggression have been found to be higher in women with compared to without PTSD (Kirby et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These findings concur with previous research that identified strong relations between PTSD severity and problematic technology use, specifically smartphone addiction (Contractor, Weiss, Tull, & Elhai, 2017). It has been suggested that PTSD and problematic smartphone use share common risk factors (Contractor, Frankfurt, Weiss, & Elhai, 2017), such as low self‐esteem, impulsivity, and neuroticism. A strong association has also been reported between PTSD severity and verbal aggression (Byrne & Riggs, 1996), and levels of verbal aggression have been found to be higher in women with compared to without PTSD (Kirby et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, excessive use of the Internet may be coping efforts with negative feelings such as PTSD symptoms in the name of self-medication. On the other hand, excessive use of the Internet may be the cause of PTSD [28] and also PTSD symptoms may be triggered by the images and sounds, that vulnerable individual sees or hears in the Internet, which may be related with their trauma. As a result, the relationship between PTSD symptoms and IASS can be bi-directional.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD is a serious and often chronic response to overwhelmingly stressful events [25] and according to Epidemiology of DSM-5 Drug Use Disorder study [26], PTSD symptoms is also related with 12-month and lifetime SUD. Furthermore, PTSD symptoms are not only related with SUD, but they are also related with behavioural addictions such as gambling [27] and problematic smartphone [28]. People with PTSD may be at risk for behavioural addictions as a means of coping with their symptoms [28].…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Still, not many studies have used a CFA approach to verify the NMP-Q as a means of understanding the addictive nature of cellphones. One of the few studies that examined addictive behavior and cellphones argued that addictive behaviors were attributed to coping mechanisms that are a part of common symptomology related to mental health adversities such as post-traumatic stress disorder (PTSD) ( Contractor et al., 2017 ). Contractor et al.…”
Section: Theorymentioning
confidence: 99%